2021
DOI: 10.3390/ijerph182413123
|View full text |Cite
|
Sign up to set email alerts
|

Electric and Manual Oral Hygiene Routines Affect Plaque Index Score Differently

Abstract: This cross-sectional study aimed to examine the oral hygiene behaviors in the general population and identify factors affecting oral hygiene behaviors and plaque removal efficacy. A survey was distributed to patients through 11 dental practices in Japan, and each patient’s plaque index score (PIS) was recorded. In total, 1184 patients participated (521 women and 660 men), with 84.04% using manual toothbrushes (MTBs) and 15.96% using electric toothbrushes (ETBs). ETB users had a significantly lower PIS compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The level of oral health literacy has a statistically significant relationship with oral health behaviors such as brushing time, use of fluoride toothpaste, and regular oral examination. Brushing is a basic technique to maintain oral health, and proper brushing can effectively remove most plaque, and research shows that the effect of brushing is closely related to the time spent brushing [ 31 , 32 ]. Based on our data analysis, we found that brushing time was associated with oral health literacy, and it was found that nurses with higher oral health literacy brushed their teeth for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The level of oral health literacy has a statistically significant relationship with oral health behaviors such as brushing time, use of fluoride toothpaste, and regular oral examination. Brushing is a basic technique to maintain oral health, and proper brushing can effectively remove most plaque, and research shows that the effect of brushing is closely related to the time spent brushing [ 31 , 32 ]. Based on our data analysis, we found that brushing time was associated with oral health literacy, and it was found that nurses with higher oral health literacy brushed their teeth for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RA patients often had oral pain or discomfort due to poor periodontal conditions and had difficulty brushing their teeth [ 20 ]; gingival bleeding also occurred while brushing teeth and was frequently diagnosed with periodontitis [ 39 ]. If brushing teeth is difficult due to joint motion restrictions, it is recommended to improve oral hygiene by the use of electric toothbrushes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study advised patients to brush their teeth for one minute per tooth. 22 The periodontium and alveolar bone change as a result of the forces used to shift teeth during orthodontic treatment. Even when a smaller orthodontic force is used for a longer period, the periodontium becomes inflamed, leading to the resorption of the alveolar bone and, ultimately, tooth displacement.…”
Section: Discussionmentioning
confidence: 99%